Врегулювання правового статусу римо-католицьких монастирів у Російській імперії (остання третина ХVIII – 50-і роки ХІХ ст.) - Кирилюк, Анна Олександрівна; Kyrylyuk, Anna O. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті проаналізовано законодавчі акти, на основі яких відбувалось врегулювання діяльності римо-католицьких монастирів в Російській імперії в останній третині ХVIII – 50-х роках ХІХ ст. Зроблено висновок, що російський уряд мав на меті встановити контроль над управлінням римо-католицькими монастирями.The article analyzes the legislative acts on which there is a regulation of activity of the Roman Catholic monasteries in the Russian Empire in the last third of the eighteenth century - the 50-ies of the XIX century, posted in the "Complete Collection of Laws of the Russian Empire." Taken into account the legislation which had been prescribed legal bases of formation control monasteries, property and economic rights of Roman Catholic monasteries, the rules of admission to the ranks of Monash. The attention is focused on the activation of the legislative activity of the Russian government after the Polish uprising of 1830-1831.which was directed at the elimination of the Roman Catholic monasteries. Concluded that the Russian government initially was intended to establish control over the management of the Roman Catholic monastery, and then eliminate them.
The Settlement of the Legal Status of Roman Catholic Monasteries in the Russian Empire (the Last Third of the Eighteenth - 50 Years of the Nineteenth Century)
Keywords: правовий статус; монастир; Російська імперія; законодавство; римо-католицький орден; legal status; monastery; Russian empire; legislation; rimo-catholic order